1991
DOI: 10.1128/jb.173.1.161-167.1991
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of an Enterobacter cloacae outer membrane protein (OmpX)

Abstract: We have described a gene coding for an Enterobacter cloacae protein, provisionally called OmpX (J. Stoorvogel, M. J. A. W. M. van Bussel, J. Tommassen, and J. A. M. van de Klundert, J. Bacteriol. 173:156-160, 1991). In the work reported here, OmpX was localized in the cell envelope by means of sucrose gradient fractionation of membrane vesicles. Overproduction of OmpX in Escherichia coli from a multicopy plasmid resulted in a reduction in the amount of OmpF. No accumulation of OmpF, of its uncleft precursor, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 30 publications
1
35
0
1
Order By: Relevance
“…K. pneumoniae ATCC 11296 was used as the reference strain in determinations of MICs for the various clinical isolates. K. pneumoniae Kp63, a porin-deficient clinical strain (2); K. pneumoniae ATCC 11296; E. coli BW5104 (26), which expresses AcrA at a basal level; and Enterobacter aerogenes ATCC 13048(pJS04) (ompX mutant with its promoter [29]), a strain that overexpresses OmpX, were used as controls for protein analysis. Bacteria were grown either in MuellerHinton (MH) broth and agar or in Luria-Bertani (LB) broth or nutrient broth (Difco Laboratories, Detroit, Mich.) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…K. pneumoniae ATCC 11296 was used as the reference strain in determinations of MICs for the various clinical isolates. K. pneumoniae Kp63, a porin-deficient clinical strain (2); K. pneumoniae ATCC 11296; E. coli BW5104 (26), which expresses AcrA at a basal level; and Enterobacter aerogenes ATCC 13048(pJS04) (ompX mutant with its promoter [29]), a strain that overexpresses OmpX, were used as controls for protein analysis. Bacteria were grown either in MuellerHinton (MH) broth and agar or in Luria-Bertani (LB) broth or nutrient broth (Difco Laboratories, Detroit, Mich.) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the expression of OmpK36 porin was elevated in all isolates, and high-osmolality conditions did not modify its biosynthesis level. Expression of OmpX has been previously reported to negatively regulate porin synthesis (29). Therefore, we determined its synthesis by immunodetection in our isolates.…”
Section: Vol 42 2004 Efflux Pumps In Resistant K Pneumoniae Isolatmentioning
confidence: 99%
“…Expression of this outer-membrane protein has been reported to regulate porin synthesis negatively at a posttranscriptional level in E. cloacae (Stoorvogel et al, 1991). We identified OmpX expression by using immunological tools.…”
Section: Detection Of Outer-mem Brane Proteinsmentioning
confidence: 99%
“…It is therefore likely that the major outer membrane protein whose level was reduced by the introduction of romA corresponds to E. coli OmpF. Stoorvogel et al (30) reported the cloning of a DNA fragment of the E. cloacae chromosome that caused an increase in the level of P-lactam resistance of host bacteria (30). This resistance was associated with a decrease in the concentration of outer membrane proteins OmpF and OmpC in E. coli and of a 37-kDa outer membrane protein in E. cloacae.…”
mentioning
confidence: 99%